Comparison of the Type and Severity of Nasal Septal Deviation between Chronic Rhinosinusitis Patients Undergoing Functional Endoscopic Sinus Surgery and Controls - Nafiseh Nikkerdar; Atena Karimi; Fatemeh Bazmayoon; Amin Golshah (International Journal of Dentistry, 2022)
Objectives. Some correlations have been proposed between chronic rhinosinusitis (CRS) and type and severity of nasal septal deviation. This study sought to compare the type and severity of nasal septal deviation between CRS patients undergoing functional endoscopic sinus surgery (FESS) and asymptomatic controls using cone-beam computed tomography (CBCT). Materials and Methods. This prospective case-control study evaluated 49 CRS patients who did not respond to pharmaceutical therapy and were candidates for FESS and 49 asymptomatic controls. All participants underwent CBCT and were inspected for septal deviation type and severity. Data were analyzed by the independent t-test and chi-square test. Results. The study population comprised of 58.25% males and 41.8% females, with a mean age of 33.74 ± 11.78 years. Significant correlations were noted between the presence of CRS and severity of septal deviation (P=0.007). Type of septal deviation had no significant correlation with the presence of CRS (P=0.443). Conclusion. Patients with CRS have significantly more severe nasal septal deviation. However, type of septal deviation is not correlated with CRS.